EEG coherence and source localization analysis during multimedia learning process - Tyng, C.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
This study aims to examine the brain dynamics in terms of EEG activity in multimedia learning using coherence and source localization analysis. EEG recording was performed on 34 participants. EEG coherence was computed over 171 pairs of electrodes across both hemispheres in different frequency bands and Low-Resolution Electromagnetic Tomography (LORETA) was applied for source analysis. The EEG coherence results showed that higher functional interaction exists between anterior-posterior long-range coherence for all four frequency bands (delta, theta, alpha and beta) for both within left and right hemispheres compared with anterior and posterior short-range coherence. Further, source localization analysis demonstrated that a significant increase in delta and theta at the bilateral frontal lobes as well as in beta activity at the left temporal lobe; while a significant decrease of alpha over right parietal, beta over frontal and posterior parieto-occipital regions during learning process. To conclude, the frontal lobe is highly recruited in multimedia learning compared with baseline eyes open. In addition, it is also actively interacting with temporal lobe and posterior parieto-occipital regions to facilitate perceptual, encoding and retrieval of prior knowledge during learning. © 2016 IEEE.